The plans they are a‐changin': More frequent iterative adjustment of regional priorities in the transition to local actions can benefit implementation. Issue 1 (9th October 2017) - Cheok, Jessica; Pressey, Robert L.; Weeks, Rebecca; VanDerWal, Jeremy; Storlie, Collin
Abstract: Aim: Regional‐scale assessments are frequently conceived to guide the strategic application of conservation actions. Although changes to priority areas from initial assessments are inevitable, the transition from regional‐scale assessment to implementing local actions is poorly understood. An outstanding question concerns the frequency with which regionally assessed priorities should be updated as actions are implemented. We address this gap by simulating the incremental implementation of local actions guided by regional conservation assessments, exploring how update frequency can influence aspects of translating regional assessments to local actions. Location: Fiji coral reefs. Methods: Our simulations were designed within the framework of systematic conservation planning, with implemented actions simulated based on conservation value in achieving objectives and feature rarity. Other decision rule‐sets were put in place to simulate on‐the‐ground negotiations that are often necessary when transitioning from regional‐scale conservation assessments to local actions. We use our simulations to evaluate how the frequency of updating regional priorities influences (1) total time taken to achieve objectives represented by numbers of planning units investigated, (2) total extent of final reserve systems and (3) spatial overlap between initial regional priorities and final implemented reserves. Results: Changes in the frequencies of updating did not influence the time taken to achieve conservation objectives, nor the total extent of final reserve systems. However, there was a significant difference in the number of times planning units were re‐investigated for implementing actions within in scenarios that involved more frequent updates. Spatial overlap between initial regional priorities and final implemented reserves increased with decreases in update frequency. Main conclusions: We find two potential benefits to updating priorities more frequently: (1) faster achievement of objectives for high‐priority features and (2) greater potential to capitalize on areas previously investigated. Our findings provide insights into trade‐offs to consider regarding the frequency of updating regional assessments, which varies depending on the planning context.